O uso de tecnologia da informação e comunicação no ensino e aprendizagem de Geografia: uma proposta de formação continuada - Pacheco, Ana Paula Pinho (2019)
This thesis sought to answer the following research problem: how can the continuous training activity, after completing the undergraduate degree in Geography, contribute positively to teachers' teaching practice, for the use of ICT in Geography teaching and learning? The question guides the path that leads to the discovery and apprehension of the challenges faced by teachers of basic education, who are indirectly stimulated in the graduation, for the use of ICT. The study object belongs to the universe of teachers trained in the Geography course, from 2011 to 2015, of the Vale do Acaraú State University - UVA, Junco campus, making a total of 132 subjects. IES is located in the municipality of Sobral and operates mainly in the northwestern portion of the State of Ceará. The general objective was to investigate and understand the attitudes of teachers of basic education in relation to the use of information and communication technologies, in the practices carried out inside and outside the classroom, as a support to the teaching and learning process of Geography; with the purpose of identifying the use, stimulating the application of ICT and proposing continuous training for their needs / realities found in the classroom from the look of the subjects surveyed. And as specific: (a) to verify the frequency and use of ICT in the process of teaching and learning in Geography, (b) to know the forms and frequency of use of Internet access by teachers of basic education, (c) used by teachers of basic education to prepare their classes and if these are used together with the students of the basic schools of northwestern Ceará, (d) identify the factors that inhibit the use of ICT in the classroom, (e) know the infrastructure (f) to identify the contribution to the teaching and learning of Geography using ICT, (g) to identify the use of ICTs, which are available to teachers of basic education to develop their professional activities, (upper level) belonging to the degree course in Geography - UVA, (h) propose a continuous training action plan, as an extensive activity of the Course of Geography - UVA, for teachers of basic education, who teach, so that they can develop skills and competences in the use of ICT. Based on the theoretical basis and analysis model, which contributes to the history of the initial course, to the need for continuous training, readings and bibliographies organized to reflect historical aspects of the evolution of technology in society, effects and advances within the context geographical. Regarding the methodological choice, a qualitative-quantitative approach was developed, developed through a case study, to treat an object within a reality not requiring control over events and behaviors, allowing to use several sources of information. The collection of the analysis material was developed from online questionnaires (IQ, QII and QIII) as a technique and semi-structured interviews, with different instruments and strategies for each one. The coding and recording of the answers were applied in a tabular matrix with the support of the statistical program Statistical Package for the Social Sciences (SPSS), version 24, whose license belongs to the University of Aveiro. And for questions related to the main question of the investigation, where the answers reached in the question regarding the teaching and learning process of Geography and the use of ICT of QIII, more care and time was devoted, since it is directly linked to the main question, which allowed us to conclude the degree of agreement and frequency of use of ICT by primary education teachers. As results, it can be seen that the subject teachers present different difficulties in the use of ICT in the classroom and articulate their contents in isolation. They are indications that their knowledge regarding the use of ICT are built in a school environment of structural deficiencies and need the support of the training institutions in order to qualify. Because of this, it is worth emphasizing the importance of discussing Continuing Education and education in general beyond the parameters of rationality, so that public policies can also invest in new ways of thinking about society, education and the subject . Therefore from the studied reality, and analyzing the parameters from the analysis of the data identified by the collection instruments and behaviors of the subjects and the lines of actions; the proposal of continuous training was built in order to develop skills and competences for the use of ICT. The proposal has a structure, five modules, organized by three levels, which are characterized by the integration of all its dimensions: skills, content, activities, theory-practice, professional training and evaluation modalities. In fact, the use of ICT occurs in an individual way for each research subject, but in recent years it has become essential in the communication between the various subjects that make up the educational process and, more generally, in society. What is in evidence is not the answer to using or not using. The fact is that technologies in their various aspects influence the form of informing and developing the forms of communication, and these are not controllable by the participants in the educational process, hence the urgency of the use. All research is of great value in the context of the institution and outside it, since they would allow to study on the subject and would establish the necessary scientific bases for the technological development of this area of study, inside and outside the classroom, with proposals of practical activities.